Optimization of Critical Parameters in Friction Stir Spot Welding of AA5052 Aluminum Alloy Using Response Surface Methodology - Mohamed M. El-Sayed Seleman; Sabbah Ataya; Nashmi H. Alrasheedi; Mohamed M. Z. Ahmed; Hagar A. Reyad; Ashraf Bakkar; Ramy A. Fouad (Crystals, 2025)
Understanding and optimizing the relationship between critical processing parameters (rotational speed and dwell time) and the resulting weld performance is crucial for the effective application of friction stir spot welding (FSSW) in joining aluminum alloys. FSSW is an increasingly important solid-state, clean technology alternative for joining lightweight alloys such as AA5052-H32 in various industries. To optimize this technique for lap joint configurations, the current study examines the influence of rotational speeds (500, 1000, and 1500 rpm) and dwell times (1, 2, and 3 s) on the heat input energy, hardness across weld zones, and tensile/shear load, using a full factorial Design-Expert (DOE) analysis. The FSSW responses of the numerical model were validated using the experimental results for the spot-welded joints. The findings indicate that the dwell time significantly affected the mechanical properties, while the tool rotational speed had a substantial effect on the heat input energy and mechanical properties. Fracture surfaces predominantly exhibited ductile failure with diverse dimple morphologies, consistent with the enhanced tensile properties under optimal parameters. The presence of finer dimples suggests a mixed-mode fracture involving shear.